2001
DOI: 10.4141/a00-057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinomycin or monensin on performance and feeding behavior of cattle fed wheat- or barley-based diets

Abstract: . 2001. Effect of salinomycin or monensin on performance and feeding behavior of cattle fed wheat-or barley-based diets. Can. J. Anim. Sci. 81: 253-261. Feeding behavior and growth performance of cattle fed diets containing monensin or salinomycin were assessed in two trials. In trial 1, 36 Hereford × Angus steers (267.7 ± 4.3 kg) were individually fed (n = 12) wheat-based transition and finishing diets containing no ionophore (control, C), 26 mg monensin (M) or 13 mg salinomycin (S) per kg of dietary dry matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
1
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
3
10
1
11
Order By: Relevance
“…0.80) due to antibiotic supplementation. Although both laidlomycin (Spires et al 1990) and monensin (Goodrich et al 1984) improve feed efficiency over control diets, response was similar when they were compared with each other (Galyean et al 1992). Both tylosin (Brown et al 1975;Vogel and Laudert 1994) and Table 2.…”
Section: Results and Discussion Performancementioning
confidence: 99%
See 4 more Smart Citations
“…0.80) due to antibiotic supplementation. Although both laidlomycin (Spires et al 1990) and monensin (Goodrich et al 1984) improve feed efficiency over control diets, response was similar when they were compared with each other (Galyean et al 1992). Both tylosin (Brown et al 1975;Vogel and Laudert 1994) and Table 2.…”
Section: Results and Discussion Performancementioning
confidence: 99%
“…Other trials have found that laidlomycin had either no effect (Berger et al 1991;Galyean et al 1992) or a positive effect on DMI (Faulkner et al 1991). In the trial of Bauer et al (1995), 12 mg kg (1 laidlomycin reduced day-to-day variation in DMI, a measurement commonly used as an indicator of acidosis (Fulton et al 1979;Stock et al 1995;Gibb et al 2001). Chlortetracycline (35 mg kg…”
Section: Results and Discussion Performancementioning
confidence: 99%
See 3 more Smart Citations